Can AI Reduce the Cost of Pharmaceutical Development? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2019)
The pharmaceutical industry has long been grappling with the dual challenges of soaring research and development (R&D) costs and protracted timelines for bri...
Keywords: Drug Discovery and Pharmaceutical AI; Reduce; Pharmaceutical; Development; Artificial Intelligence; Machine Learning; Deep Learning